EFFECT OF PROCESS PARAMETERS ON REMOVAL OF OIL FROM POME USING POLYPROPYLENE MICRO/NANOFIBER - Semilin, Veroneka; Albert, Beatcy; Janaun, Jidon (MATTER: International Journal of Science and Technology, 2018)
In the present study, the effectiveness of the micro/nanofiber to adsorb oil was evaluated by varying the process parameters such as oil concentration, time, weight of micro/nanofiber and temperature. The reusability of the micro/nanofiber was also studied. The results showed that the oil adsorption capacity of the micro/nanofiber using refined palm oil was 29.4. The oil adsorption process found that increasing on oil concentration, weight of micro/nanofiber and contact time showed increasing in oil removal (%), but increasing in temperature showed reduction in oil removal (%). The performance of micro/nanofiber in oil removal after pressing technique were decreased. However, solvent washing helps to regenerate the micro/nanofiber and increased the oil removal performance. Therefore, it was concluded that the polypropylene micro/nanofiber had been demonstrated to be effective in removing oil from POME.